Management Evaluation of Swimming Sports Development Program in Spectrum Club, Semarang City (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The achievement of swimming in which the coaching and management factors are very important. Achievement of achievements in a comprehensive concept of a tiered coaching and management pattern, so that the process gets excellent results and use as evaluation material. This study aims to evaluate: Context, Input, Process, and Products related to the swimming coaching program management at the Semarang City Spectrum Club. This research method uses a qualitative approach with the CIPP evaluation model (context, input, process, product), data collection techniques use observation, interviews, documentation and data combination / triangulation.The results include context, implementing the coaching program is under the background, vision-mission and objectives of the coaching program that has been carried out, Input, has good human resources, appropriateness of facilities and infrastructure is not good, and funding sources have limitations. The process, implementing the training program, athlete recruitment was going well, the use of facilities and infrastructure is good, coordination between related parties is also good, and the welfare is running well, Product, swimming performance at the Spectrum club in Semarang City is good but not optimal and still not stable in achieving achievements in each race. This study concludes that from the context and process aspects it is good, while the input feasibility of facilities and infrastructure is not good, the product, the achievement is good enough because it often participates in both regional and national competitions, but achievement is not optimal and to maintain achievement is still not stable.